Acute pontine infarction inducing REM sleep behavior disorder: a novel case report - Wang, Liuqing; Wang, Hong (Frontiers in Human Neuroscience, 2025)
Rapid eye movement (REM) sleep behavior disorder (RBD) is parasomnia characterized by the loss of physiological muscle atonia during REM sleep, resulting in dream-enacting behaviors that often manifest as complex, violent motor activity. While RBD may occur idiopathically, it is frequently associated with neurodegenerative disorders, particularly α-synucleinopathies such as Parkinson’s disease. However, secondary RBD linked to acute cerebrovascular events remains poorly documented. Here, we present a novel case of acute pontine infarction precipitating RBD, highlighting the brainstem’s critical role in REM sleep regulation and expanding the spectrum of secondary RBD etiologies. This case report underscores the importance of neuroanatomical localization in evaluating acute-onset RBD, particularly in the context of cerebrovascular pathology.